1970
DOI: 10.3329/dujbs.v21i1.9741
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis Of Three Surface-Water Gley Soils From The Meghna Floodplain Of Bangladesh

Abstract: Surface-water gley soils comprise extensive area on the seasonally wet landscape of Meghna floodplain in Bangladesh. Three typical surface-water gley soils from the above floodplain were studied in the field and laboratory for their pedogenesis. Morphological properties indicate that there is formation of gleyed/ pseudogleyed horizons in the soil profiles. Extensive development of mottles, ploughpans and flood coatings or gleyans is the most notable morphogenetic features in these soils. Physically, these soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…The low pH in topsoils may be attributed to low amounts of bases caused by leaching during fluctuations of water table and percolation of water during flooding periods, removal of bases through crop harvests and farming practices. [27] Observed similar trend of pH increasing with depth in annually flooded soils of Bangladesh. Likewise, [34] reported a similar trend of soil pH increasing with depth in paddy soils of Kilombero Valley.…”
Section: Soil Reaction (Ph) Organic C Total N Organicsupporting
confidence: 52%
See 2 more Smart Citations
“…The low pH in topsoils may be attributed to low amounts of bases caused by leaching during fluctuations of water table and percolation of water during flooding periods, removal of bases through crop harvests and farming practices. [27] Observed similar trend of pH increasing with depth in annually flooded soils of Bangladesh. Likewise, [34] reported a similar trend of soil pH increasing with depth in paddy soils of Kilombero Valley.…”
Section: Soil Reaction (Ph) Organic C Total N Organicsupporting
confidence: 52%
“…All the pedons had abundant redoximorphic features in form of strong brown (iron) mottles due to the reducing/waterlogged soil conditions. Researchers [25,26,27] observed similar mottles respectively in subsoils of floodplains in Nigeria and in surface-water grey soils in Bangladesh. Horizon boundary attributes varied among and within pedons, whereby distinctness ranged from abrupt to gradual, but topography was dominantly smooth.…”
Section: Soil Morphology and Genesis Of The Studied Soils In Kilombermentioning
confidence: 90%
See 1 more Smart Citation
“…The strong to medium acid observed in the tops soils of these profiles could be ascribed to low amount of bases by leaching during water table fluctuations and water percolation during flooding periods and soil nutrients mining [36,39,40]. The data also showed that pH increased with depth in the studied profiles as likewise reported in [41,42]. The nature of the observed acidity in the top soils of the representative profiles threatens the availability of mineral elements such as P which is readily available in soils with pH centred at 6.5.…”
Section: 31soil Phsupporting
confidence: 65%
“…The fact that in each MAP zone this ratio decreased with soil depth rather steadily and within rather narrow ranges (Fig. 3e) indicates top-down pedogenesis from an initially texturally uniform material (Khan et al, 2012). Therefore, although some Croatian Stagnosols may be polygenetic (Rubinić et al, 2015), most seem to be formed primarily by normal pedogenesis.…”
Section: Particle Size Distribution Of the Investigated Pseudogley Prmentioning
confidence: 92%